The role of chemoradiotherapy in the treatment of neuroendocrine rectal cancer: case reports - S. S. Gordeev; A. Seidinovich; A. A. Naguslayeva; S. B. Polikarpova; Z. Z. Mamedli (Сибирский онкологический журнал)
The aim of the study was to assess the response to preoperative radiotherapy (RT) in patients with G2-G3 rectal neuroendocrine tumors (NETs). Material and methods. Case reports involving patients who were given treatment at the N.N. Blokhin National Medical Research Center of Oncology from 2000 to 2020 were retrospectively studied. Patients with histologically verified neuroendocrine tumors of the rectum and anal canal (G2 and G3, Ki67>3%), who underwent preoperative radiotherapy (RT) or chemoradiotherapy (CRT) were included into the study. the study excluded patients who received palliative RT/CRT, patients with primary multiple synchronous or metachronous tumors, and patients with unresectable liver metastases. Staging was performed on the basis of MRI of the pelvis, CT scan of the chest and abdomen with intravenous contrast. The main assessment parameter was the response rate to treatment according to the RECIST criteria, and additional parameters were the frequency of pathological response according to DWORAK classification and overall and relapse-free survivals. Statistical analysis was conducted using the IBM SPSS software package (version 25). Results. The median follow-up time was 24 months. the follow-up time of a patient with G3 neuroendocrine cancer was 64 months without the evidence of disease progression. The 5-year OS and DFS for patients with G2-G3 rectal NETs were 64.3 % and 53.3 %, respectively. Conclusion. Long-term progression-free survival in 2 out of 3 patients with G3 neuroendocrine cancer (1 of them with a complete clinical response) and in 3 out of 4 patients with G2 neuroendocrine tumors was obtained.